AN EXPLORATION INTO THE INFLUENCES OF CULTURE ON THE RELATIONSHIPS OF CHINESE AND BRITISH CONSUMERS WITH BRANDS - Ochen, Eunice (2006)
According to studies of culture such as Hofstedes (1991) cultural dimensions, Chinese and British culture are very different. The Chinese culture is viewed as more traditional whereas the British culture is seen as more modern.